Low-dose computed tomography for lung cancer screening in Anhui, China: A randomized controlled trial - Rong, Feng; Shi, Rui; Hu, Lili; Chen, Ran; Wang, Daoyue; Lv, Xiazhi; Zhao, Yong; Huang, Wei; Yang, Yang; Zhou, Hongyang; Hong, Kaige (Frontiers in Oncology, 2022)
Background: Lung cancer is the leading cause of cancer-related death worldwide, with risk factors such as age and smoking. Low-dose computed tomography screening can reduce lung cancer mortality. However, its effectiveness in Asian populations remains unclear. Most Asian women with lung cancer are non-smokers who have not been screened. We conducted a randomized controlled trial to evaluate the effectiveness of low-dose computed tomography screening in a Chinese population, including high-risk smokers and non-smokers exposed to passive smoking. The baseline data are reported in this study. Methods: Between May and December 2019, eligible participants were randomized in a ratio of 1:1:1 to a screening (two arms) or control cohort. Non-calcified nodules/masses with a diameter >4 mm on low-dose computed tomography were considered positive findings. Results: In total, 600 patients (mean age, 59.1±6.9 years) underwent low-dose computed tomography. Women accounted for 31.5% (189/600) of patients; 89.9% (170/189) were non-smokers/passive smokers. At baseline, the incidence of lung cancer was 1.8% (11/600). The incidence of lung cancer was significantly lower in smokers than in female non-smokers/passive smokers (1.0% [4/415] vs. 4.1% [7/170], respectively; P=0.017). Stage 0–I lung cancer accounted for 90.9% (10/11) of cases. Conclusions: We demonstrate the importance of including active smokers and female non-smokers/passive smokers in lung cancer screening programs. Further studies are needed to explore the risk factors, and long-term cost–benefit of screening Asian non-smoking women.